Behavior Management of Children with Autism - Al – Rawi, Baydaa Ali Othman (AL-Kindy College Medical Journal, 2019)
Background: Pervasive Developmental Disorder (PDD) is a term refers to the overarching group of conditions to which autism spectrum disorder (ASD) belongs . Objective: This study was designed to determine the existing behavior of children with autism in dental sitting, the behavior improvements in recall dental visits and evaluate the improvement in oral hygiene with using specific visual pedagogy chart. Type of the study: Cross-sectional study. Methods: Forty children of both genders, ages ranged from 4 – 6 years having primary teeth only were selected whose medical history included a diagnosis of autism. The behavior of the children in dental sitting were assessed according to the Frankel scale. The dmft index in the first visit was measured, with codes and criteria established by the WHO(1997).Behavior management method used was one or more of the followings: (physical restraint, "Tell-Show-Feel and Do" technique, verbal and non – verbal communication, reinforcement, parent present / absent). Results: The samples represent by 22 males and 18 females autistic children with no statically significant difference (p> 0.05).The dmft index of autistic children in the first visit. The dmft (mean ± SD) for males was (7.818 ± 0.98) while for females was (6.922 ± 1.09).The frequency of children showed treatment acceptance without difficulty was increase in the recall visits. Conclusions: The dental professional should be flexible to modify the treatment approach according to the individual patient needs.